Manajemen Asuhan Kebidanan Antepartum Ny ”R” Gestasi 7 Minggu 2 Hari dengan Emesis Gravidarum di UPT Puskesmas Bajoe Kabupaten Bone: Antepartum Midwife Care Management Ny "R" Gestation 7 Weeks 2 Days with Emesis Gravidarum at UPT Puskesmas Bajoe, Bone District - Muchtar, Asrianti Safitri; Rasyid, Indah Nirmala (Jurnal Midwifery, 2023)
Introduction Emesis gravidarum is a feeling of nausea felt by pregnant women which is then caused by increased levels of human chorionic ganadotrophin in serum and also the hormone estrogen during pregnancy. The hCG hormone is what will stimulate the production of the hormone estrogen in the ovaries. According to the 2016 World Health Organization (WHO) states that cases of nausea and vomiting can occur in at least 14% of all ecosystems of women during pregnancy obtained from all over the world. And 60-80% of it, namely in primigravidas and 40-60% of it in multigravida pregnancies. Carrying out care management for clients with cases of emesis gravidarum is a very important thing to do. So that the purpose of taking this case is to carry out management of antepartum midwifery care Mrs "R" gestation 7 weeks 2 days with emesis gravidarum at UPT Puskesmas Bajoe Bone Regency in 2022. Method This study uses Varney’s 7-step midwifery care management method and SOAP. Result In the evaluation of the results of midwifery care carried out on Mrs "R" gestation 7 weeks 2 days with emesis gravidarum which was carried out from 24 May 2022 to 07 June 2022 experienced progress, judging from the goals and criteria that had been planned previously, it could be resolved properly. Conclusion The case study by conducting an assessment in the form of management of midwifery care for clients with emesis gravidarum at UPT Puskesmas Bajoe, Bone Regency, has carried out studies, analysis, and documentation related to all actions that have been carried out with the results not finding any gaps between the theory and the cases obtained